Geographical Information System based assessment of spatiotemporal characteristics of groundwater quality of upland sub-watersheds of Meenachil River, parts of Western Ghats, Kottayam District, Kerala, India - H. Vijith R. Satheesh
Hydrogeochemistry of groundwater in upland sub-watersheds of Meenachil river, parts of Western Ghats, Kottayam, Kerala, India was used to assess the quality of groundwater for determining its suitability for drinking and agricultural purposes. The study area is dominated by rocks of Archaean age, and Charnonckite is dominated over other rocks. Rubber plantation dominated over other types of the vegetation in the area. Though the study area receives heavy rainfall, it frequently faces water scarcity as well as water quality problems. Hence, a Geographical Information System (GIS) based assessment of spatiotemporal behaviour of groundwater quality has been carried out in the region. Twenty-eight water samples were collected from different wells and analysed for major chemical constituents both in monsoon and postmonsoon seasons to determine the quality variation. Physical and chemical parameters of groundwater such as pH, dissolved oxygen (DO), total hardness (TH), chloride (Cl), nitrate (NO3) and phosphate (PO4) were determined. A surface map was prepared in the Arc-GIS 8.3 (spatial analyst module) to assess the quality in terms of spatial variation, and it showed that the high and low regions of water quality varied spatially during the study period. The influence of lithology over the quality of groundwater is negligible in this region because majority of the area comes under single lithology, i.e. charnockite, and it was found that the extensive use of fertilizers and pesticides in the rubber, tea and other agricultural practices influenced the groundwater quality of the region. According to the overall assessment of the basin, all the parameters analysed are below the desirable limits of WHO and Indian standards for drinking water. Hence, considering the pH, the groundwater in the study area is not suitable for drinking but can be used for irrigation, industrial and domestic purposes. The spatial analysis of groundwater quality patterns of the study area shows seasonal fluctuations and these spatial patterns of physical and chemical constituents are useful in deciding water use strategies for various purposes.